Structural Reassignment of Two Polyenol Natural Products. Issue 9 (3rd February 2023) - Kutateladze, Andrei G.; Bates, Roderick W.; Elyashberg, Mikhail; Williams, Craig M.
Abstract: Unusual polyenols that defied chemical principles were reassigned as the nucleosides, adenosine and uridine, using a combination of chemical intuition underpinned by Computer Assisted Structure Elucidation (CASE) and DFT methods. Abstract : Chemical principles together with CASE and DFT methods were used to reassign unusual polyenols as nucleosides.